The Age Limit for Marriage in Brunei Darussalam in Maslahah and Legal Politics Perspectives - Liky Faizal; Abd Qohar (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, Indonesia, 2021)
Brunei Darussalam which embraces Islamic law reform must be carried out in line with what is the goal of Islamic law itself, which is to fulfill the demands of the instincts of human life, and must be based on maslahah which is in line with the principles of maqoshid al-shari'ah and in accordance with the objectives law in the legal system. The formulation of the problem in this article was related to the age limit of marriage in Brunei Darussalam in the perspective of law and politics. The purpose of this research was to understand the legal and political review of the legal determination of the age limit of marriage in Brunei Darussalam. The research type was library research, by collecting data obtained from library research sourced from several books, theses, journals and articles related to the title to be discussed. This research used a juridical, normative, philosophical, and historical approach that served as the answer and solution to the problems that exist in the community and state. The results of this research were that the application of the concept of maslahah to the minimum age limit for marriages in Brunei Darusslam had not been carried out optimally because the country had local wisdom that was still considered in accordance with the context of their respective countries. In the political perspective of legal regulations the minimum age of marriage in Brunei Darussalam still needed to be improved in its justice, legal certainty, and legal usefulness.